(3TQM GdCQLhRI GdjGSejfIs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3YHO Gddg Hf GdMLGL Hf EHQGgje Hf GdGeGe GdYdhjs ((3LGeY GdCRgQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LHQ bdhH ChdjGFg CeG HYO agPG GdJYdjb eNJUQ Ci NeSGFd Yde GdLHQ hJSei VQhHkG OGFQI Ydi KdGKI CfhGY abW hgj GdYOO hGdLPQ hGdeGd s
(3BNQgG (B:s
(3hhLhg GdJNjd ef NhGU GdYOO Ef de Jcf eSJMjdI hbO jXgQ dc GSJMGdJgG HGdfXQ ajgG hai gPG GdbOQ GdPi ChQOJg caGjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B63s
Keywords: (3GdQjGVjGJs